Longitudinal Validation of a Specific Measure of Fear Avoidance in Athletes: Predicting Time from Injury to Return to Sports Competition - Tito N; Porter E; Castonguay T; Dover G (Journal of Pain Research, 2023)
Noémie Tito, Erica Porter, Tristan Castonguay, Geoffrey Dover Department of Health, Kinesiology, and Applied Physiology, Concordia University, Montreal, QC, CanadaCorrespondence: Geoffrey Dover, Department of Health, Kinesiology, and Applied Physiology, Concordia University, 7141 Sherbrooke Street West, Montreal, QC, Canada, Tel +1 514 848 2424 Ext 3304, Fax +1 514 848 8681, Email geoffrey.dover@concordia.caPurpose: We developed the Athlete Fear Avoidance Questionnaire (AFAQ) to measure fear avoidance in athletes. Previous fear avoidance scales were developed for the general population and have demonstrated significant predictive capabilities regarding rehabilitation. No research to date has examined the association between athlete fear avoidance as measured by the AFAQ and the rehabilitation time in athletes.Patients and Methods: Fifty-nine athletes who were injured during sport season participated in the study (40 males and 19 females). At injury onset, all participants completed self-report functional questionnaires. In addition, we measured multiple aspects of fear avoidance including athlete fear avoidance (AFAQ), kinesiophobia (TSK), and pain catastrophizing (PCS). Finally, we assessed pain severity and interference, as well as depression. Once the athletes were able to return to competition all participants answered the questionnaires again. Pearson correlations and a regression analysis were used to identify relationships between function, psychological variables, pain, and return to competition time.Results: The AFAQ yielded the strongest correlation with return to competition time (r=0.544, p< 0.001). In addition, function at initial injury time and pain interference were also significantly correlated with return to competition time (r=0.442, p< 0.001 and r=0.356, p=0.006 respectively). Athlete fear-avoidance combined with function at the time of injury explained 34% of the variance of return to competition time in the multivariate regression model (p< 0.001).Conclusion: Athlete fear-avoidance as measured by the AFAQ is associated with rehabilitation time and returning to competition in injured athletes. Psychosocial factors including athlete fear avoidance may explain why some athletes take longer to rehabilitate than others and should be evaluated in athletes who are taking longer than anticipated to complete their rehabilitation. Reducing athlete fear avoidance may facilitate rehabilitation in future studies.Keywords: catastrophizing, kinesiophobia, psychosocial factors, rehabilitation